Demokrasi Patronase dan Praktik Politik Uang: Pengalaman Pemilu Legislatif 2014 di Kota Pelembang, Sumatera Selatan - Mahsun, Muhammad (JPW (Jurnal Politik Walisongo), 2020)
This study reveals the practices of money politics which took place in Indonesia’s electoral democracy and political network that helps the working of its parctices. The analysis unit of this study is based on practices of money politics conducted by the candidates in Palembang constituences for the South Sumatera provincial parliament in 2014 legislative election. Using qualitative method and political patronage theory, the important findings of this study reveals that money politics in 2014 legislative election becomes the dominan instrument used by candidates (incumbent and new comers) to mobilize electoral support, rather than ideology and programatic politics of the party and candidates. The practice of money politics is working in networks of political clientelism among candidates, brokers and voters are built through bonds of kinship, frienship and figures